Long-term prescribing of benzodiazepines in community psychiatry clinics in the Johannesburg Health District - Tau, Machipi Alice (My University, 2024)
Background Anecdotal evidence indicates that the prevalence of long-term benzodiazepine prescription in the Johannesburg health district is high and not in accordance with accepted prescribing guidelines. Aim This study aimed to determine the prevalence of long-term prescriptions of benzodiazepines in community psychiatry clinics in Johannesburg during 1st January to 30th June 2019 and to determine, if any, associations between demographic and clinical variables and long-term prescriptions. Setting Five of the 27 community psychiatry clinics in the Johannesburg Health District were randomly selected. The clinics included in the study were Discoverers, Eldorado Park Ext 8, Crosby, Zola, and Hillbrow. Methods A descriptive, retrospective and cross-sectional record review was conducted. Clinical records of 126 adult patients above 18 years were reviewed. Descriptive statistics were presented as proportions and percentages. Odds Ratios calculated from Fischer's exact tests described the association between long-term benzodiazepines and the demographic and clinical variables. Results The study population comprised of 126 patients. Approximately one out of every four patients (23.8%; n=30) were prescribed benzodiazepines. Most of the patients were males (56.7%) aged between 18 and 50 years (56.7%), single (60.0%), and unemployed (63.3%). The most common psychiatric diagnoses were bipolar disorders (33.3%) and psychotic disorders (23.3%). The majority had no comorbid medical illnesses (56.7%) nor substance use (80.0%). The most common benzodiazepine prescribed was clonazepam at relatively low dosages. Ninety-three percent of the patients had been prescribed benzodiazepines for the long-term (more than 180 days). There were no statistically significant associations between this prescribing pattern and any sociodemographic and clinical factors (p>0.05). Conclusion This study found that approximately one in four patients (23.8%) attending community psychiatry clinics in the Johannesburg Health District were prescribed benzodiazepines. Nearly all these prescriptions were long-term (over 180 days), and no statistically significant associations between this practice and any sociodemographic and clinical factors could be established.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Psychiatry clinics; Johannesburg Health District; Benzodiazepines; SDG-3: Good health and well-being